Risk of second primary cancer among breast cancer patients: A systematic review and meta-analysis - Parhizgar, Parynaz; Bahadori Monfared, Ayad; Mohseny, Maryam; Keramatinia, Aliasghar; Hashemi Nazari, Seyed Saeed; Rahman, Syed Azizur; Al Marzouqi, Amina; Al-Yateem, Nabeel; Mosavi Jarrahi, Alireza (Frontiers in Oncology, 2023)
Objectives The aim of this study was to estimate the extra risk of second primary cancer among breast cancer patients. Methods and materials This is a systematic review. A comprehensive search of literature was performed in PubMed, Web of Science, Cochrane library, and Scopus. The search included all published studies up to October 2022. This systematic review included studies published in the English language that reported the risk of second primary non-breast cancer [i.e., standardized incidence ratio (SIR)] among breast cancer patients older than 15 years. After evaluating the methodological quality of the selected studies, SIRs were pooled with consideration of heterogeneity among studies. The estimates were pooled by age and time since the diagnosis of primary breast cancer for both sexes (male and female). Age was categorized based on before 50 years and after 50 years, and time was categorized as duration of less than and more than 10 years, respectively. Results From 2,484 articles, 30 articles were eligible for inclusion in the systematic review and meta-analysis. The studies varied in terms of population, number of cases, study design, setting, and year of implementation of the research. The estimated SIR for men and women was 1.28 (95% CI: 1.18, 1.38) and 1.27 (95% CI: 1.15, 1.39), respectively. Women diagnosed with breast cancer before menopause [SIR: 1.52 (95% CI: 1.34, 1.71) vs. 1.21 (95% CI: 1.08, 1.34)] as well as women after 10 years since their breast cancer diagnosis [1.33 (95% CI: 1.22, 1.431) vs. 1.24 (95% CI: 1.10, 1.37)] were at a higher risk of developing second primary cancer. Among men, while there were no differences in risk based on age, with the increase of time, the risk of second primary cancer was reduced [SIR: 1.22 (95% CI: 1.12, 1.33) vs. 1.00 (95% CI: 0.79, 1.22)]. Conclusion There is an extra risk of second primary cancer among breast cancer patients. The extra risk should be considered for further screening and preventive measures among this population. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=336062, identifier (CRD42022336062).